Development and reliability of a 7×15m repeated on-ice sprint test for female ice hockey players - Wilson, K.; Jackson, J.; Snydmiller, G.; Bell, G. (International Journal of Exercise Science, 2021)
The purpose of this investigation was to design and examine the reliability of a 7×15m repeated on-ice skating sprint test for female ice hockey players. Seventeen women (? ± SD age, height and body mass = 21 ± 2 years, 166.2 ± 6.4 cm and 61.9 ± 7.7 kg, respectively) completed 7 consecutive on-ice sprints of 15m repeated every 15s. Two trials of the test were performed on the same day and then repeated on a different day approximately 1 week later for a total of 4 trials. The fastest 15m time, mean time for 7 sprints and total sprint time collapsed across all 4 trials was 2.96 ± 0.12s, 3.05 ± 0.13s and 21.35 ± 0.89s, respectively. There were no significant differences between trials for any variable. Typical error (TE), coefficient of variation (%CV) and intra-class coefficients (ICC) for the fastest 15m time, mean of 7 sprints, and total time were ICC = 0.77, TE = 0.06s and %CV = 2.1; ICC = 0.91; TE = 0.04s and %CV = 1.4; and, ICC = 0.91; TE = 0.29 and %CV = 1.4 for all 4 trials, respectively. Players in the forward position had a faster mean 15m time and lower total time compared to those in the defensive position (p < 0.05). These findings show that a 7×15m repeated on-ice sprint test for varsity women ice hockey players was reliable. It was also found that forwards had a better mean of 7 sprint time and faster total time compared to players in the defensive position.